Serum Concentration of Bone Metabolism Biomarkers in Goats during the Transition Period - Mohamed Tharwat (Veterinary Medicine International)
Objective. During the transition period, the animal experiences a series of nutritional, physiological, and social changes. The objective of the present study was to evaluate the influence of the periparturient period in goats on the serum concentrations of the bone biomarkers osteocalcin (OC), bone-specific alkaline phosphatase (b-ALP), and pyridinoline cross-links (PYD). Method. Blood samples were collected from fifteen female goats during the periparturient period 3 wk before expected parturition (T −3), within 12 h of parturition (T 0), and 3 wk after parturition (T +3). Results. Compared to a value of 77.67 ± 47.6 ng/mL at T −3, the serum concentrations of OC measured 51.91 ± 22.09 ng/mL at T 0 and 72.61 ± 35.21 ng/mL at T +3. A comparison of OC values at T −3, T 0, and T +3 did not reveal any significant difference (P>0.05). Compared to a value of 42.00 ± 19.50 U/L at T −3, the serum concentration of b-ALP measured 32.49 ± 15.41 U/L at T 0 and 34.31 ± 18.89 U/L at T +3. A comparison of b-ALP values at T −3, T 0, and T +3 did not reveal any significant difference (P>0.05). Compared to a value of 17.86 ± 9.15 nmol/L at T −3, the serum concentration of PYD decreased significantly at T 0 to a value of 7.48 ± 4.50 nmol/L (P<0.0001). At T +3, the PYD serum concentration measured 7.72 ± 2.91 nmol/L, which differed significantly from T −3 values (P<0.05). Conclusion. The results of this study showed that the bone formation biomarkers (OC and b-ALP) did not change significantly during the periparturient period, while the bone resorption biomarker decreased significantly at parturition compared to 3 wk before and 3 wk after parturition. The significantly increased serum estrogen around parturition may have had a role in the increased bone resorption at this time.